Optimizing rivaroxaban therapy through therapeutic drug monitoring (TDM): A review article - Almas, A Made Dea; Purukan, Juliana; Supardi, Widhowati (Indonesian Journal of Pharmacology and Therapy, 2024)
Therapeutic drug monitoring (TDM) is a technique used to measure and analyze plasma drug concentrations to optimize dosages for individual patients. The goal is to maintain drug concentration within target ranges to maximize therapeutic effects and prevent side effects. Rivaroxaban, a popular direct oral anticoagulant (DOAC) could cause risks such as drug interactions and bleeding. Therapeutic drug monitoring can help mitigate these risks by ensuring personalized and appropriate dosing for the individual patient. Within 2-4 hr after a dose, rivaroxaban reaches peak concentrations due to its rapid absorption with nearly perfect absorption at a 10 mg dose. Its pharmacodynamic effects are dose-dependent. There are no significant interactions between rivaroxaban and NSAIDs like naproxen or acetylsalicylic acid. Rivaroxaban exhibits potential for clinically significant interactions with drugs that inhibit CYP3A/P-gp pathways or possess antithrombotic properties. Notably, co-administration with strong P-gp/BCRP and CYP3A4 inhibitors, such as ketoconazole and ritonavir, can lead to a substantial increase in rivaroxaban exposure.